IMPLEMENTASI APLIKASI BANTUAN SEBAGAI PEMAHAMAN PENGGUNA PADA WEB UKM SUYTEESTORE: IMPLEMENTATION BUILD APPLICATION USER GUIDE HELP FOR UNDERSTANDING USERS OF WEB UKM SUYTEESTORE - Ariadi Retno Hayati; Habibie Ed; Wilda Imama Sabilla; Vit Zuraida; Candra Bella (LPPM Universitas Abdurrab, 2024)
This activity research implementation application with tools help for users implementation based web for UKM SuyteeStore in Malang. This application have content for understanding by user how to operate the application web for catalogue and order system where each content has explanation for each content as detailed in web based. Design in this application has simply design and easy understanding for users with HTML and PHP programming. The contents of help application in this application are information how to access web for the use of find products and detailed product as catalogue product, the use how to order in system, the use of how process after order in system, the information of UKM SuyteeStore and location and contact and the information in this application can help users to operate the web that building for catalogue and order system in application web based. This application is build as tool for user that link to web UKM SuyteeStore and help users to understand the contents in application web UKM SuyteeStore with different menus and content in this tools application as sub of the web in UKM SuyteeStore. This application is designed with the concept of theory for build application for users as help user guide that in the concept of build application user guide must be have fews contents that different with the application and the contents must be explanation the application contents as detail.